Spatio-Temporal Analysis of PM10 in Southern Peninsular Malaysia - Saiful Mohamad Khir, Mohamad; Muda, Khalida; Hussein, Norelyza; Faisal Abdul Khanan, Mohd; Nor Othman, Mohd; Hashim, Normala; Dahari, Nadhira (International Journal of Engineering and Technology, 2018)
In this study, the particulate matter with diameter less than 10 micrometers (PM10) is being observed. Other factors that influenced the pollutant dispersion are also being studied prior to identification of their relationship. The aim of this study is to identify the trend of PM10 concentrations in the Southern Peninsular of Malaysia during the period 2005 to 2015 by using spatio-temporal analysis in regards to air pollution. The inverse distance weighted (IDW) is used for the spatio interpolation data and mapping. The trends of the PM10 concentration are illustrated via map which indicates the affected and vulnerable area of Southern Peninsular Malaysia especially during Haze episode.Â Â